Analysis of Critical Thinking Ability in Solving Linear Programming Problems in terms of Students' Self-Concepts - Permatasari, Dwi; Nurhanurawati, Nurhanurawati (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
The complex internal process of learning is very closely related to thinking because complex activities and closely related to one another is a way of thinking to solve problems and produce something. This article aims to analyze critical thinking skills in solving linear program questions in terms of students' self-concept. This type of research is qualitative research with a case study method. The research subjects were five students of IPA vocational high school. The instruments used were tests, interviews, and questionnaires. The results showed that students with high self-concept, the ability to think critically in solving linear program questions were still low, the low ability to think critically of students in solving questions was still a lot of errors including: (1) Writing incorrect, incorrect and unsystematic concepts, (2) The picture is incomplete, (3) on the student's answer sheet, (4) write down the reasons for the arguments that are still unclear, while the results of the interview show the students can verbally convey answers in solving linear program problems. Proses internal yang kompleks dalam belajar sangat erat dengan adanya berpikir, karena kegiatan yang kompleks dan berhubungan erat satu dengan yang lain merupakan cara berpikir untuk memecahkan masalah dan menghasilkan sesuatu. Artikel ini bertujuan untuk menganalisis kemampuan berpikir kritis dalam menyelesaikan soal program linear ditinjau dari konsep diri peserta didik. Jenis penelitian ini adalah penelitian kualitatif dengan metode studi kasus. Subjek penelitian adalah lima peserta didik SMA jurusan IPA. Instrument yang digunakan adalah tes, wawancara dan angket. Hasil penelitian menunjukkan bahwa peserta didik dengan konsep diri positif kemampuan berpikir kritis dalam menyelesaikan soal program linear masih rendah, rendahnya kemampuan berpikir kritis peserta didik dalam menyelesaikan soal masih banyak kesalahan diantaranya: (1) Penulisan konsep yang tidak tepat, tidak benar dan tidak sistematis, (2) Gambar yang kurang lengkap, (3) pada lembar jawaban peserta didik, (4) menuliskan alasan argumentasi yang masih kurang jelas, sedangkan hasil wawancara menunjukkan peserta didik mampu menyampaikan secara lisan jawaban dalam menyelesaikan masalah program linear.